Impact of Guided Inquiry with Simulations on Knowledge of Electricity and Wave Phenomena - Espinoza , Fernando (European Scientific Journal, ESJ, 2020)
The impact of inquiry-based instruction on the improvement of content knowledge of electricity and wave properties in two studies was the subject of this investigation. Groups of pre-college and undergraduate students performed a series of tasks designed to determine the effectiveness of exploratory/investigative approaches to the study of wave properties in fostering content retention and conceptual change, as well as in comparison with traditionally performed experimental activities. The results show that a guided inquiry-based method using simulations significantly improves content performance on electricity and wave motion, although not in optics; in particular, it helps students to visualize charge exchanges and electric neutrality, the shape of electric fields, types of waves and their characteristics, and the effects of the transmitting medium on the speed of a wave. Additionally, its exploratory nature is superior to the confirmatory laboratory experience, both in content retention and in facilitating the incorporation of perceptual features that help learners deal with documented challenging properties of waves.